PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN MODAL INTELEKTUAL (Studi Pada Perusahaan Go Public Yang Tergabung Dalam Indeks LQ45 Tahun 2011 Sampai 2012) (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the effect of firm characteristics on the level of intellectual capital disclosure. This analysis uses the independent variable is the size of the company, profitability, leverage, business age, ownership structure, independent and dependent variable level of disclosure of intellectual capital. The sample used is secondary data from the Indonesia Stock Exchange ( IDX ) that the Annual Report of listed companies in LQ45 and listing in 2011 and 2012 in IDX . Samples were taken by purposive sampling method , and who meet the criteria for sample selection. The samples are 59 companies. The results of the analysis is based on the use of all the independent variables indicate that the size of the company have a significant effect on the disclosure of intellectual capital , while profitability , leverage , listing age , ownership structure , and independent commissioner had no significant effect on the disclosure of intellectual capital.Keywords: Intellectual Capital Disclosures, Firm Size, Profitability, Leverage, Listing Age, Ownership Structure, and Independent Commissioner